Optical transparent adhesive sheet, laminate, and stuck structure

A multi-layered adhesive sheet with acrylic layers and ultraviolet protection addresses peeling and bubble issues in resin panels, ensuring high adhesion and ultraviolet resistance in harsh environments.

JP2025014054AInactive Publication Date: 2025-01-28BANDO CHEM IND LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024192886
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing optical transparent adhesive sheets face issues with peeling, bubble formation, and reduced adhesive force in high temperature and high humidity environments, particularly when used with resin panels, and lack sufficient ultraviolet protection.

Method used

A multi-layered optical transparent adhesive sheet structure comprising a first and second acrylic adhesive layer with an intermediate layer, containing ultraviolet absorbers and specific moisture permeability, to enhance adhesion and resist environmental stress.

Benefits of technology

The adhesive sheet maintains high adhesion, prevents bubble formation, and provides ultraviolet protection, ensuring reliability and visibility in high temperature and humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014054000001_ABST
    Figure 2025014054000001_ABST
Patent Text Reader

Abstract

To provide an optical transparent adhesive sheet which has high adhesion on an adhesive interface between a resin panel and an OCA sheet, and has followability to expansion / contraction of an adherend, adequate moisture permeability, and high weather resistance and ultraviolet ray blocking capability that are usable as on-vehicle applications, a laminate using the same, and a stuck structure using the same.SOLUTION: An optical transparent adhesive sheet has a first acrylic adhesive layer constituting a first surface, an intermediate adhesive layer, and a second acrylic adhesive layer constituting a second surface in this order, wherein the first acrylic resin agent layer and the second acrylic resin agent layer are blended with 0.1 to 3 pts.wt. of an ultraviolet ray absorber with respect to 100 pts.wt. of an acrylic resin, total thickness is 200 to 2,100 μm, and adhesive force is 20 N / 25 mm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optically transparent adhesive sheet, a laminate having the optically transparent adhesive sheet, and a laminated structure having the optically transparent adhesive sheet. [Background technology]

[0002] Optically clear adhesive (OCA) sheets are transparent adhesive sheets used to bond optical components. An example of the use of OCA sheets is in a display device, where they are used to bond a display panel such as a liquid crystal module to a cover panel that is provided on the top surface of the display device. The OCA sheet fills the space between the display panel and the cover panel, improving the visibility of the screen of the display panel.

[0003] Examples of documents disclosing prior art in the field related to OCA sheets include the following patent documents. Patent Document 1 relates to a pressure-sensitive adhesive sheet for a display screen, a laminate, a display using the same, and a screen protection method thereof, and discloses a pressure-sensitive adhesive sheet for a display screen, which has a pressure-sensitive adhesive layer (B1) formed from a pressure-sensitive adhesive composition (x) containing a resin (b1) and an ultraviolet absorber (triazine-based, etc.) on one side of a transparent substrate (A), and a pressure-sensitive adhesive layer (B2) formed from a pressure-sensitive adhesive composition (y) containing a resin (b2) on the other side of the transparent substrate (A). It also discloses that blue light can be shielded by having a pressure-sensitive adhesive layer formed from a pressure-sensitive adhesive composition containing a specific amount of ultraviolet absorber relative to the resin.

[0004] Patent Document 2 discloses an adhesive tape in which a resin layer of at least one type selected from acrylic resins, polyester resins, and urethane resins and an adhesive layer of at least one type selected from acrylic resins, polyester resins, and urethane resins are laminated. The resin layer and adhesive layer are formed by laminating on a release sheet, and the adhesive tape is laminated in the order of release sheet, resin layer, adhesive layer, and release sheet, and it is disclosed that an ultraviolet absorber is used in the resin layer and the adhesive layer.

[0005] Patent Document 3 discloses an optically transparent adhesive sheet having, in this order, a first surface adhesive layer, an intermediate adhesive layer, and a second surface adhesive layer, the storage moduli of the first surface adhesive layer and the second surface adhesive layer at 85°C being higher than the storage modulus of the intermediate adhesive layer at 85°C, the storage moduli of the first surface adhesive layer and the second surface adhesive layer at 85°C being 3.0×104 Pa or more and 30.0×104 Pa or less, the storage modulus of the intermediate adhesive layer at 85°C being 1.0×104 Pa or more and 15.0×104 Pa or less, and the intermediate adhesive layer containing polyurethane, with the objective of providing an optically transparent adhesive sheet which is excellent in flexibility and which suppresses the generation of delay bubbles in high temperature and high humidity environments.

[0006] Meanwhile, with the diversification of display devices, the use of resin panels as cover panels, which are more advantageous in terms of design, safety (shatterproof when broken) and cost than the conventional glass panels, has been considered in recent years. For this reason, OCA sheets are required to have transparency and sufficient adhesive strength to various materials. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-179242 A [Patent Document 2] JP 2016-155958 A [Patent Document 3] International Publication No. 2019 / 026577 Summary of the Invention [Problem to be solved by the invention]

[0008] In order to realize an OCA sheet suitable for bonding a display panel and a touch panel body, the present inventors have been developing an OCA sheet having a multilayer structure in which a first acrylic adhesive layer, an intermediate adhesive layer, and a second acrylic adhesive layer are laminated. The OCA sheet having this multilayer structure can obtain excellent adhesion due to the first and second acrylic adhesive layers, and therefore can exhibit excellent properties such as resistance to peeling due to shear stress.

[0009] However, when a laminated structure made by bonding this multi-layered OCA sheet with a resin panel is placed in a high-temperature environment (high temperature: 95°C, high temperature and high humidity: 85°C / 85%) during an in-vehicle reliability test, problems such as lifting due to outgassing from the resin panel, peeling due to bubbles, and whitening due to the high temperature and humidity environment can occur. Bubbles that are not present immediately after bonding at the adhesive interface between the OCA sheet and the resin panel but are generated later are called delayed bubbles, and are thought to be caused by the phenomenon in which the surface with weak adhesive strength peels off due to the pressure of water vapor generated from the resin panel.

[0010] In addition, there has been a demand for an OCA sheet having ultraviolet ray blocking ability, and a laminated structure in which OCA sheets having ultraviolet ray degradation suppressed are bonded together.

[0011] The present invention has been made in consideration of the above-mentioned current situation, and aims to provide an optically transparent adhesive sheet that has high adhesive strength at the adhesive interface between a resin panel and an OCA sheet, and also has the ability to follow the expansion and contraction of the adherend, moderate moisture permeability, and high weather resistance and UV protection ability that makes it suitable for in-vehicle use, as well as a laminate using the same and a bonded structure using the same. [Means for solving the problem]

[0012] The present inventors have studied the above problems and focused on making the optically transparent adhesive sheet have a multi-layer structure in order to achieve high adhesive strength and follow the expansion and contraction of the adherend. The present inventors have also further studied the suppression of delay bubbles and prevention of whitening in a high temperature and high humidity environment of a laminated structure using the optically transparent adhesive sheet, and found that the generation of delay bubbles and whitening can be suppressed in a high temperature and high humidity environment by providing a first acrylic adhesive layer and a second acrylic adhesive layer containing an acrylic resin and an ultraviolet absorber, thereby completing the present invention.

[0013] The optically transparent adhesive sheet of the present invention comprises, in that order, a first acrylic adhesive layer constituting a first surface, an intermediate adhesive layer, and a second acrylic adhesive layer constituting a second surface, and the first acrylic resin layer and the second acrylic resin layer are blended with 0.1 to 3 parts by weight of an ultraviolet absorber per 100 parts by weight of acrylic resin, have a total thickness of 200 to 2100 μm, and have an adhesive strength of 20 N / 25 mm or more.

[0014] The optically transparent adhesive sheet preferably has a haze of less than 2%.

[0015] The first acrylic resin agent layer and the second acrylic resin agent layer have moisture permeability, and the moisture permeability is 400 to 800 g / m 2 It is preferable that:

[0016] The intermediate pressure-sensitive adhesive layer preferably contains a urethane elastomer and / or an acrylic elastomer.

[0017] The laminate of the present invention is characterized in that it is composed of the optically transparent adhesive sheet of the present invention, a first release film covering one side of the optically transparent adhesive sheet, and a second release film covering the other side of the optically transparent adhesive sheet.

[0018] The laminated structure of the present invention is characterized by having a resin substrate adhered to a first surface of the optically transparent adhesive sheet of the present invention. Effect of the Invention

[0019] According to the optically transparent adhesive sheet of the present invention, an optically transparent adhesive sheet having high adhesive strength at the adhesive interface between the resin substrate and the OCA sheet, and having the ability to follow the expansion and contraction of the adherend, moderate moisture permeability, and high weather resistance usable for in-vehicle use can be obtained, and an optically transparent adhesive sheet having ultraviolet ray blocking ability and suppressed whitening in a high temperature and high humidity environment can be obtained. According to the laminate of the present invention, the handleability of the optically transparent adhesive sheet of the present invention can be improved and ultraviolet ray blocking ability can be imparted. According to the laminate structure of the present invention, peeling is unlikely to occur even in a high temperature and high humidity environment, the occurrence of delay bubbles and whitening in a high temperature and high humidity environment are suppressed, and a laminate structure having high weather resistance usable for in-vehicle use and suppressed ultraviolet ray degradation can be obtained. [Brief description of the drawings]

[0020] [Figure 1] A cross-sectional view showing a schematic diagram of an example of the optically transparent adhesive sheet of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view illustrating a schematic example of a laminate of the present invention. [Diagram 3] FIG. 2 is a schematic diagram for explaining a method for evaluating adhesive strength. [Figure 4] A cross-sectional view showing a schematic example of a display device with a touch panel using the optically transparent adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] [Optical transparent adhesive sheet] The optically transparent adhesive sheet of the present invention has a first acrylic adhesive layer, an intermediate adhesive layer, and a second acrylic adhesive layer in this order, and the first acrylic adhesive layer and the second acrylic adhesive layer are blended with 0.1 to 3 parts by weight of an ultraviolet absorber per 100 parts by weight of acrylic resin, and are characterized by having a total thickness of 200 to 2100 μm and an adhesive strength of 20 N / 25 mm or more.

[0022] Fig. 1 is a cross-sectional view showing a schematic example of an optically transparent adhesive sheet of the present invention. As shown in Fig. 1, the optically transparent adhesive sheet 10 of the present invention has, in this order, a first acrylic adhesive layer 11 constituting a first surface (adhesive surface), an intermediate adhesive layer 12, and a second acrylic adhesive layer 13 constituting a second surface (adhesive surface). In addition, the intermediate adhesive layer 12 is preferably thicker than the first acrylic adhesive layer 11 and the second acrylic adhesive layer 13. By having such a laminated structure, even when the adherend is a resin panel, high adhesive strength can be obtained at the adhesive interface, and the sheet can deform in accordance with the expansion and contraction of the adherend.

[0023] <Acrylic adhesive layer> The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 are layers containing an acrylic resin. The acrylic resin is obtained by curing an acrylic resin composition. Examples of the acrylic resin composition include those containing a (meth)acrylic acid ester polymer or a copolymer thereof (hereinafter also referred to as a (meth)acrylic copolymer) and a crosslinking agent.

[0024] The (meth)acrylic copolymer may be, for example, a copolymer of an alkyl (meth)acrylate ester and a carboxyl group-containing monomer.

[0025] The (meth)acrylic acid alkyl ester includes (meth)acrylic acid alkyl esters having an alkyl group with 1 to 18 carbon atoms (CH2=CR1-COOR2; R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group with 1 to 18 carbon atoms), and the alkyl group preferably has 4 to 12 carbon atoms.

[0026] Examples of the (meth)acrylic acid alkyl esters having an alkyl group of 1 to 18 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undeca (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate. These may be used alone or in combination of two or more.

[0027] Examples of the carboxyl group-containing monomer include carboxyl group-containing (meth)acrylates such as β-carboxyethyl (meth)acrylate, 5-carboxypentyl (meth)acrylate, succinic acid mono(meth)acryloyloxyethyl ester, and ω-carboxypolycaprolactone mono(meth)acrylate; acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid, and maleic acid. These may be used alone or in combination of two or more.

[0028] As the crosslinking agent, for example, a component capable of causing a crosslinking reaction with the crosslinkable functional group derived from the crosslinkable functional group-containing monomer possessed by the (meth)acrylic copolymer can be used, and specific examples thereof include isocyanate compounds, metal chelate compounds, epoxy compounds, etc. The crosslinking agents may be used alone or in combination of two or more kinds.

[0029] The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 may contain polyurethane. The polyurethane is obtained by curing a polyurethane composition. The polyurethane composition may be, for example, a thermosetting polyurethane composition. The thermosetting polyurethane composition may be the same as the thermosetting polyurethane composition used in the intermediate pressure-sensitive adhesive layer 12 described below.

[0030] It is preferable that the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 have moisture permeability. Since the first surface and the second surface form an adhesive interface with an adherend, when the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 constituting the first surface and the second surface have moisture permeability, water vapor, which is thought to be a cause of the generation of delayable bubbles, is less likely to accumulate at the adhesive interface, and the generation of delayable bubbles can be further suppressed. The moisture permeability can be measured in accordance with JIS Z0208.

[0031] The moisture permeability can be adjusted by the composition of the acrylic resin constituting the first acrylic adhesive layer 11 and the second acrylic adhesive layer 13. For example, a method is generally known in which the acrylic resin is constituted by a copolymer and the proportion of components that contribute to moisture permeability is adjusted (see JP 2015-227395 A and JP 5,920,519 B).

[0032] The moisture permeability of the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 is 400 to 800 g / m 2It is preferable that the moisture permeability is in the above range. This is because when a laminated structure using the optically transparent adhesive sheet 10 is placed in a high temperature and high humidity environment (85°C, 85%) for a long period of time (for example, 1000 hours), the occurrence of delay bubbles can be sufficiently suppressed. The moisture permeability is 450 to 750 g / m 2 It is more preferable that:

[0033] The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 have an adhesive strength to glass of 20 N / 25 mm or more at room temperature (23° C.). In this specification, the adhesive strength refers to a measured value in a 180° peel test. The test method for the 180° peel test may be any method that complies with JIS Z2037, and details will be described later. The upper limit of the adhesive strength at room temperature is not particularly limited, but is, for example, 100 N / 25 mm.

[0034] FIG. 3 is a schematic diagram for explaining the method for evaluating adhesive strength. The above 180° peel test will be explained using FIG. 3. First, an optically transparent adhesive sheet 10 cut to a length of 75 mm x width of 25 mm is used as a test piece. One side of this test piece is attached to a slide glass 31 having a length of 75 mm x width of 25 mm, and the optically transparent adhesive sheet 10 and the slide glass 31 are bonded together by holding the slide glass 31 at a pressure of 0.4 MPa for 30 minutes. Next, as shown in FIG. 3(a), a PET sheet 32 ​​is bonded to the surface of the optically transparent adhesive sheet 10 opposite to the slide glass 31. After that, after leaving the sheet at a predetermined temperature for a certain period of time, as shown in FIG. 3(b), the PET sheet 32 ​​is pulled in the 180° direction, the optically transparent adhesive sheet 10 is peeled off at the interface with the slide glass 31, and the adhesive strength of the optically transparent adhesive sheet 10 to the slide glass 31 is measured. As the PET sheet, for example, a PET sheet having a thickness of 125 μm ("Melinex (registered trademark) S" manufactured by Teijin DuPont Films) or the like can be used.

[0035] The thickness of the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 is preferably 3 to 100 μm. If the thickness is less than 3 μm, there is a risk that sufficient adhesive strength for sufficiently suppressing delayed bubbles cannot be obtained. On the other hand, if the thickness exceeds 100 μm, there is a risk that flexibility (step-following ability) sufficient to follow and deform along steps present on the surface of the adherend to which the optically transparent pressure-sensitive adhesive sheet is attached cannot be obtained. In addition, when the optically transparent pressure-sensitive adhesive sheet is used to bond substrates having different elasticity when the environment changes, such as bonding a glass substrate and a resin substrate, there is a risk that the optically transparent pressure-sensitive adhesive sheet cannot follow the dimensional change of the substrate when the environment changes and may peel off. The thickness of the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 is more preferably 3 to 40 μm.

[0036] The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 contain an ultraviolet absorbing agent. As the ultraviolet absorbing agent, for example, a benzotriazole-based ultraviolet absorbing agent, a triazine-based ultraviolet absorbing agent, a benzophenone-based ultraviolet absorbing agent, etc. are used, and a benzotriazole-based ultraviolet absorbing agent and a triazine-based ultraviolet absorbing agent are preferable. If a benzotriazole-based ultraviolet absorbing agent or a triazine-based ultraviolet absorbing agent is used, compatibility with the acrylic resin is sufficiently ensured, so that the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 having good weather resistance and ultraviolet ray blocking ability can be obtained.

[0037] The benzotriazole-based ultraviolet absorber is not particularly limited, and various types can be used. For example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-tert-octyl- 6-Benzotriazolylphenol), polyethylene glycol ester of 2-(2-hydroxy-3-tert-butyl-5-carboxyphenyl)benzotriazole, 2-[2-hydroxy-3-(2-acryloyloxyethyl)-5-methylphenyl]benzotriazole, 2-[2-hydroxy-3-(2-methacryloyloxyethyl)-5-tert-butylphenyl]benzotriazole, 2-[2-hydroxy-3-(2-methacryloyloxyethyl)-5-tert-octyl 2-[2-hydroxy-3-(2-methacryloyloxyethyl)phenyl]benzotriazole, 2-[2-hydroxy-3-tert-butyl-5-(2-methacryloyloxyethyl)phenyl]benzotriazole, 2-[2-hydroxy-3-tert-butyl-5-(2-methacryloyloxyethyl)phenyl]benzotriazole, 2-[2-hydroxy-3-tert-amyl-5-(2-methacryloyloxyethyl)phenyl] Benzotriazole, 2-[2-hydroxy-3-tert-butyl-5-(3-methacryloyloxypropyl)phenyl]-5-chlorobenzotriazole, 2-[2-hydroxy-4-(2-methacryloyloxymethyl)phenyl]benzotriazole, 2-[2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropyl)phenyl]benzotriazole, 2-[2-hydroxy-4-(3-methacryloyloxypropyl)phenyl]benzotriazole, etc. These benzotriazole-based ultraviolet absorbers may be used alone or in combination of two or more.

[0038] The triazine-based ultraviolet absorber is not particularly limited, and various types can be used. For example, 2-(4,6-diphenyl-1,3,5-triazine-2-yl-5)-[2-(2-ethylhexanoyloxy)ethoxy]phenol, 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4- butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine. These triazine-based ultraviolet absorbers may be used alone or in combination of two or more.

[0039] The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 are preferably formed by blending 0.1 to 3 parts by weight of an ultraviolet absorbing agent with respect to 100 parts by weight of an acrylic resin. If the blending amount of the ultraviolet absorbing agent is less than 0.1 parts by weight with respect to 100 parts by weight of an acrylic resin, the effect of improving weather resistance and ultraviolet blocking ability may not be sufficiently obtained. On the other hand, if the blending amount of the ultraviolet absorbing agent is more than 3 parts by weight with respect to 100 parts by weight of an acrylic resin, the transparency of the optically transparent pressure-sensitive adhesive sheet 10 may not be sufficiently obtained.

[0040] <Intermediate adhesive layer> The intermediate adhesive layer 12 preferably contains a urethane-based elastomer and / or an acrylic-based elastomer, which makes it possible to obtain an optically transparent adhesive sheet 10 having excellent transparency and conformability.

[0041] When the intermediate adhesive layer 12 contains a urethane-based elastomer, it is preferable that it contains polyurethane. Since polyurethane is flexible, the optically transparent adhesive sheet 10 of the present invention stretches well when a tensile stress is applied, and is very difficult to tear. Therefore, it can be peeled off without leaving any adhesive residue. Furthermore, polyurethane has a high dielectric constant, and the optically transparent adhesive sheet 10 using polyurethane as the intermediate adhesive layer 12 can obtain a high electrostatic capacitance. Therefore, an optically transparent adhesive sheet in which the intermediate adhesive layer 12 contains polyurethane can be suitably used for bonding a capacitance type touch panel. Furthermore, since the intermediate adhesive layer 12 contains polyurethane, excellent transparency is ensured, and the occurrence of whitening can be suppressed even under high temperature and high humidity environments.

[0042] When the intermediate adhesive layer 12 contains a urethane-based elastomer, it is preferable that it contains a thermosetting polyurethane. The thermosetting polyurethane is a cured product of a thermosetting polyurethane composition. Since the thermosetting polyurethane can be formed into a film without using a solvent, the intermediate adhesive layer 12 can be made thick by containing the thermosetting polyurethane. In addition, the intermediate adhesive layer 12 contains a thermosetting polyurethane, so that even if it is formed into a thick film, it is possible to obtain a highly reliable optically transparent adhesive sheet that has excellent flexibility and transparency, and is unlikely to whiten even under high temperature and high humidity environments. The thermosetting polyurethane composition preferably contains a polyol component and a polyisocyanate component. The thermosetting polyurethane is obtained, for example, by reacting a polyol component with a polyisocyanate component, and preferably has a structure shown in the following formula (A).

[0043] [ka]

[0044] In the above formula (A), R represents the moiety excluding the NCO group of the polyisocyanate component, R' represents the moiety excluding the OH group of the polyol component, and n represents the number of repeating units.

[0045] The thermosetting polyurethane is preferably not acrylic-modified, and preferably does not contain a site derived from an acrylic acid ester, a methacrylic acid ester, or the like in the main chain. When the thermosetting polyurethane is acrylic-modified, it is hydrophobic, and therefore moisture tends to aggregate under high temperature and high humidity. This moisture aggregation may cause whitening, foaming, or the like, and impair the optical properties. Therefore, by making the thermosetting polyurethane not acrylic-modified, it is possible to prevent the deterioration of the optical properties due to whitening, foaming, or the like under high temperature and high humidity. The thermosetting polyurethane is preferably such that the total amount of the monomer units derived from the polyol component and the monomer units derived from the polyisocyanate component is 80 mol % or more of the monomer units constituting the entire thermosetting polyurethane.

[0046] The polyol component and the polyisocyanate component can be liquid at room temperature (23°C), and a thermosetting polyurethane can be obtained without using a solvent. Other components such as a tackifier can be added to either the polyol component or the polyisocyanate component, and are preferably added to the polyol component. When preparing the intermediate adhesive layer 12, it is not necessary to remove the solvent, so a uniform sheet can be formed thick. In addition, the intermediate adhesive layer 12 can maintain its optical properties even when formed thick, and coloring and foaming (the generation of bubbles at the interface with the adherend) can be sufficiently suppressed. Furthermore, the intermediate adhesive layer 12 can be made thick and is flexible, so it has excellent impact resistance. The optically transparent adhesive sheet provided with the intermediate adhesive layer 12 can be used to bond a transparent member having a transparent conductive film on its surface to a cover panel, and when another member is used, it can also be used to bond a display panel or a transparent member having a transparent conductive film on its surface to another member. When an optically transparent adhesive sheet with an intermediate adhesive layer 12 is used to bond a display panel to a transparent member (touch panel) having a transparent conductive film on its surface, the step formed by the bezel positioned on the outer edge of the display panel can be covered by the optically transparent adhesive sheet.

[0047] The polyol component is not particularly limited, and examples thereof include polyether polyols, polycaprolactone polyols, polycarbonate polyols, polyester polyols, etc. These may be used alone or in combination of two or more kinds.

[0048] The polyol component preferably has an olefin skeleton. That is, the main chain is preferably composed of polyolefin or a derivative thereof. Examples of the polyol component having an olefin skeleton include polybutadiene polyols such as 1,2-polybutadiene polyol, 1,4-polybutadiene polyol, 1,2-polychloroprene polyol, and 1,4-polychloroprene polyol, polyisoprene polyols, and polyols whose double bonds are saturated with hydrogen or halogen. The polyol component may be a polyol obtained by copolymerizing an olefin compound such as styrene, ethylene, vinyl acetate, or acrylic ester with a polybutadiene polyol or a hydrogenated product thereof. The polyol component may have a linear structure or a branched structure. Only one type of the polyol component may be used, or two or more types may be used. The polyol component used in the polyurethane preferably contains 80 mol % or more of a polyol component having an olefin skeleton, and more preferably consists of only a polyol component having an olefin skeleton.

[0049] The polyisocyanate component is not particularly limited, and a conventionally known polyisocyanate can be used. Either or both of a hydrophilic polyisocyanate having a hydrophilic unit and a hydrophobic polyisocyanate having no hydrophilic unit may be used. The hydrophilic polyisocyanate having the hydrophilic unit does not mean a polyisocyanate having improved hydrophilicity only by a structure derived from an isocyanate group such as an isocyanurate structure or a biuret structure, but a polyisocyanate having a functional group (hydrophilic unit) that enhances hydrophilicity. The inclusion of a hydrophilic unit in the polyisocyanate component provides an effect of suppressing whitening due to moisture absorption.

[0050] The hydrophilic unit is preferably a polyalkylene oxide unit. Examples of the polyalkylene oxide unit include a polyethylene oxide unit and a polypropylene oxide unit. The content of the polyalkylene oxide unit is preferably 0.1% by weight or more and 20% by weight or less based on the total weight of the thermosetting polyurethane composition. If the content is less than 0.1% by weight, the effect of suppressing whitening may not be sufficiently obtained. If the content exceeds 20% by weight, the compatibility with low-polarity olefin polyol components, tackifiers, plasticizers, etc. may decrease, and optical properties such as haze may decrease. The content of the polyalkylene oxide unit is more preferably 0.1 to 5% by weight. If the content exceeds 5% by weight, the amount of moisture absorption in the high-temperature and high-humidity environment may be too large.

[0051] Examples of hydrophilic units other than polyalkylene oxide units include units containing a carboxylic acid group, an alkali metal salt of carboxylic acid, a sulfonic acid group, an alkali metal salt of sulfonic acid, a hydroxyl group, an amide group, an amino group, etc. More specifically, examples include polyacrylic acid, an alkali metal salt of polyacrylic acid, a sulfonic acid group-containing copolymer, an alkali metal salt of a sulfonic acid group-containing copolymer, polyvinyl alcohol, polyacrylamide, carboxymethylcellulose, an alkali metal salt of carboxymethylcellulose, polyvinylpyrrolidone, etc.

[0052] The polyisocyanate component is preferably a modified polyisocyanate obtained by reacting an aliphatic and / or alicyclic polyisocyanate having an isocyanate group with an ether compound having a polyalkylene oxide unit. By using an aliphatic and / or alicyclic polyisocyanate, coloring and discoloration are less likely to occur, and the transparency of the optically transparent adhesive sheet can be more reliably ensured over a long period of time. In addition, by making a modified product by reacting an ether compound having a polyalkylene oxide unit, the polyisocyanate component can suppress whitening due to the action of the hydrophilic portion (polyalkylene oxide unit), and can exhibit compatibility with low-polarity tackifiers, plasticizers, etc. due to the action of the hydrophobic portion (other units).

[0053] The thermosetting polyurethane composition preferably has an α ratio (molar number of OH groups derived from the polyol component / molar number of NCO groups derived from the polyisocyanate component) of 1 or more. When the α ratio is less than 1, the amount of the polyisocyanate component is excessive relative to the amount of the polyol component, so that the thermosetting polyurethane becomes hard, and it may be difficult to ensure the flexibility required for the optically transparent adhesive sheet. If the flexibility of the intermediate adhesive layer 12 is low, it is not possible to cover the unevenness and steps present on the bonding surface, particularly when bonding an optical member such as a touch panel. In addition, when the α ratio is less than 1, there is a risk that the adhesive strength required for the optically transparent adhesive sheet cannot be ensured. The above α ratio is preferably less than 2.0. When the α ratio is 2.0 or more, the thermosetting polyurethane composition may not be sufficiently cured.

[0054] The thermosetting polyurethane composition may further contain a plasticizer. The plasticizer is not particularly limited as long as it is a compound used to impart flexibility to the thermosetting polyurethane, but from the viewpoints of compatibility and weather resistance, it is preferable to contain a carboxylic acid-based plasticizer.

[0055] The thermosetting polyurethane composition may further contain a catalyst. The catalyst is not particularly limited as long as it is a catalyst used in a urethanization reaction, and examples thereof include organic tin compounds such as di-n-butyltin dilaurate, dimethyltin dilaurate, dibutyltin oxide, and tin octanoate; organic titanium compounds; organic zirconium compounds; tin carboxylates; bismuth carboxylates; and amine catalysts such as triethylenediamine.

[0056] When the intermediate pressure-sensitive adhesive layer 12 contains an acrylic elastomer, the acrylic elastomer may be any acrylic elastomer that is commonly used in the technical field to which the present invention pertains, without any particular limitation. The intermediate pressure-sensitive adhesive layer composition may be prepared using a commercially available acrylic elastomer (e.g., SK Dyne 1875 (manufactured by Soken Chemical Industries, Ltd.)).

[0057] The thickness of the intermediate adhesive layer 12 is preferably 100 to 2000 μm. If the thickness is less than 100 μm, the flexibility of the entire optically transparent adhesive sheet is reduced, and when one side of the optically transparent adhesive sheet is attached to the surface of an optical member, the optically transparent adhesive sheet cannot cover the unevenness or steps present on the surface of the optical member, and the other side of the optically transparent adhesive sheet and the surface of the other optical member may not be attached with sufficient adhesive strength. If the thickness exceeds 2000 μm, optical properties such as haze and total light transmittance may not be sufficiently obtained. The more preferable lower limit of the thickness of the intermediate adhesive layer 12 is 200 μm, and the even more preferable lower limit is 250 μm. The more preferable upper limit of the thickness of the intermediate adhesive layer 12 is 1500 μm, and the even more preferable upper limit is 1000 μm.

[0058] The optically transparent adhesive sheet 10 only needs to have the first acrylic adhesive layer 11, the intermediate adhesive layer 12, and the second acrylic adhesive layer 13 in this order, and may further have other layers. The first acrylic adhesive layer 11 and the second acrylic adhesive layer 13 only need to be located on the outermost surface (the surface in contact with the adherend) of the optically transparent adhesive sheet 10. Furthermore, it is preferable that the first acrylic adhesive layer 11 and the intermediate adhesive layer 12 are in contact with each other, and it is preferable that the second acrylic adhesive layer 13 and the intermediate adhesive layer 12 are in contact with each other.

[0059] The intermediate adhesive layer composition constituting the intermediate adhesive layer 12 may contain various additives such as tackifiers (tackifiers), colorants, stabilizers, antioxidants, antifungals, and flame retardants, as necessary, within the limits that do not impair the required properties of the optically transparent adhesive sheet.

[0060] In addition, an ultraviolet absorber may be added to the above-mentioned composition for the intermediate adhesive layer to the extent that it does not impair the required properties of the optically transparent adhesive sheet, but it is preferable that it does not contain an ultraviolet absorber from the standpoint of reducing the haze of the optically transparent adhesive sheet and suppressing the occurrence of delay bubbles in high temperature and high humidity environments (85°C 85%).

[0061] <Optical transparent adhesive sheet> In order to ensure the performance as an optically transparent adhesive sheet, the optically transparent adhesive sheet 10 of the present invention preferably has a haze of less than 2%, more preferably 1% or less, and even more preferably 0.5% or less. The optically transparent adhesive sheet 10 preferably has a total light transmittance of 90% or more. In addition, in order to ensure the performance as an optically transparent adhesive sheet, each of the first acrylic adhesive layer 11, the intermediate adhesive layer 12, and the second acrylic adhesive layer 13 preferably has a haze of less than 2% and a total light transmittance of 90% or more, and more preferably has a haze of 1% or less and a total light transmittance of 90% or more. The haze and total light transmittance can be measured, for example, using a turbidity meter "HazeMeter NDH2000" manufactured by Nippon Denshoku Industries Co., Ltd. The haze is measured by a method conforming to JIS K 7136, and the total light transmittance is measured by a method conforming to JIS K 7361-1.

[0062] The total thickness of the optically transparent adhesive sheet 10 of the present invention is 200 to 2100 μm. If the total thickness is less than 200 μm, the flexibility of the optically transparent adhesive sheet 10 decreases, and when one side of the optically transparent adhesive sheet is attached to the surface of an optical member, the optically transparent adhesive sheet cannot cover the unevenness or steps present on the surface of the optical member, and the other side of the optically transparent adhesive sheet and the surface of the other optical member may not be attached with sufficient adhesive strength. If the total thickness exceeds 2000 μm, optical properties such as haze and total light transmittance may not be sufficiently obtained. A more preferable lower limit of the total thickness of the optically transparent adhesive sheet 10 is 250 μm. In addition, it is even more preferable that the total thickness of the optically transparent adhesive sheet 10 exceeds 250 μm.

[0063] The method for laminating the first acrylic adhesive layer 11, the intermediate adhesive layer 12, and the second acrylic adhesive layer 13 in this order is not particularly limited, and examples include a method in which the first acrylic adhesive layer 11, the second acrylic adhesive layer 13, and the intermediate adhesive layer 12 are separately prepared and then bonded together.

[0064] The method for producing the first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 is not particularly limited, and may be, for example, a method using a general-purpose film-forming device or film-forming method such as various coating devices, bar coaters, doctor blades, etc. The first acrylic pressure-sensitive adhesive layer 11 and the second acrylic pressure-sensitive adhesive layer 13 may also be produced by centrifugal molding.

[0065] The method for producing the intermediate pressure-sensitive adhesive layer 12 is not particularly limited, and examples of the method include a method in which a composition for the intermediate pressure-sensitive adhesive layer is prepared, and then the composition is molded while being thermally cured by a conventionally known method. For example, when the composition for the intermediate pressure-sensitive adhesive layer is a thermosetting polyurethane composition, the method preferably includes a step of preparing a thermosetting polyurethane composition by stirring and mixing a polyol component, a polyisocyanate component, and a tackifier, and a step of curing the thermosetting polyurethane composition.

[0066] When the intermediate adhesive layer composition is a thermosetting polyurethane composition, a specific example of the manufacturing method is to first prepare a master batch by adding a predetermined amount of tackifier to a polyol component, and dissolving it by heating and stirring. Next, the obtained master batch, polyol component, polyisocyanate component, silane coupling agent, and other components such as a catalyst as necessary are mixed and stirred with a mixer or the like to obtain a liquid or gel-like thermosetting polyurethane composition. Thereafter, the thermosetting polyurethane composition is immediately put into a molding device, and the thermosetting polyurethane composition is moved while being sandwiched between the first and second release films to cause a curing reaction (crosslinking reaction), thereby semi-curing the thermosetting polyurethane composition and obtaining a sheet integrated with the first and second release films. Then, the intermediate adhesive layer 12 is obtained by causing a crosslinking reaction in an oven for a certain period of time.

[0067] Even when the intermediate adhesive layer composition contains an acrylic elastomer, the intermediate adhesive layer composition containing the acrylic elastomer can first be prepared, and then the intermediate adhesive layer 12 can be formed by thermally curing the composition, for example.

[0068] [Laminate] A release film may be attached to both sides of the optically transparent adhesive sheet of the present invention. FIG. 2 is a cross-sectional view showing a schematic example of the laminate of the present invention. A laminate 20 (hereinafter also referred to as the "laminate of the present invention") in which the optically transparent adhesive sheet 10 of the present invention, a first release film 21 covering one side of the optically transparent adhesive sheet 10, and a second release film 22 covering the other side of the optically transparent adhesive sheet 10 are laminated is also one aspect of the present invention. According to the laminate of the present invention, both sides of the optically transparent adhesive sheet of the present invention can be protected by the first release film and the second release film until just before being attached to the adherend. This prevents a decrease in adhesion to the optically transparent adhesive sheet of the present invention and adhesion of foreign matter. In addition, the optically transparent adhesive sheet of the present invention is prevented from adhering to anything other than the adherend, thereby improving handleability.

[0069] Examples of the first release film and the second release film include a PET film, etc. The material and thickness of the first release film and the second release film may be the same or different from each other.

[0070] The bonding strength (peel strength) of the optically transparent adhesive sheet and the first release film of the present invention and the bonding strength (peel strength) of the optically transparent adhesive sheet and the second release film of the present invention are preferably different from each other. By having different bonding strengths, only one of the first release film and the second release film (the release film with the lower bonding strength) is peeled off from the laminate of the present invention, and the first surface of the exposed optically transparent adhesive sheet is bonded to the first adherend, and then the other of the first release film and the second release film (the release film with the higher bonding strength) is peeled off, and the second surface of the exposed optically transparent adhesive sheet is easily bonded to the second adherend.

[0071] At least one of the surface of the first release film that contacts the optically transparent adhesive sheet of the present invention and the surface of the second release film that contacts the optically transparent adhesive sheet of the present invention may be subjected to an easy peeling treatment (release treatment). Examples of the easy peeling treatment include silicon treatment.

[0072] [Laminated structure] The laminated structure of the present invention may have a configuration including a resin substrate adhered to the first surface of the optically transparent adhesive sheet. A glass substrate may be adhered to the second surface of the optically transparent adhesive sheet, or a resin substrate identical to and / or different from the resin substrate may be adhered. The resin constituting the resin substrate adhered to the first surface of the optically transparent adhesive sheet is not particularly limited, and examples thereof include polycarbonate, polymethylmethacrylate resin (PMMA), triacetyl cellulose (TAC), polyethylene terephthalate (PET), and the like. In addition, the resin constituting the resin substrate adhered to the second surface of the optically transparent adhesive sheet may be the same resin as the resin constituting the resin substrate adhered to the first surface. As the resin constituting the resin substrate, polycarbonate and polymethylmethacrylate resin (PMMA) are preferable.

[0073] For example, when polycarbonate is used as the resin substrate to be adhered to the first surface of the optically transparent adhesive sheet, polycarbonate is generally a material that easily absorbs moisture, so when a structure in which a polycarbonate substrate and an optically transparent adhesive sheet are bonded together is placed in a high temperature environment, bubbles (delayed bubbles) may be generated at the interface between the polycarbonate substrate and the optically transparent adhesive sheet. In particular, in a high temperature and high humidity environment (85°C 85%), moisture absorption of the polycarbonate substrate is promoted, making delayed bubbles more likely to occur. In contrast, in the present invention, a resin substrate (e.g., a polycarbonate substrate) is bonded to the first surface constituted by the first acrylic adhesive layer, so that high adhesive strength is exhibited and the generation of delayed bubbles can be suppressed. In addition, the optically transparent adhesive sheet of the present invention has excellent weather resistance and ultraviolet ray blocking ability because the first and second acrylic resin agent layers contain an ultraviolet ray absorber, and even when the laminated structure of the present invention having this is placed in a high temperature and high humidity environment, it exhibits excellent weather resistance and ultraviolet ray degradation suppression ability. In addition, the first and second acrylic adhesive layers in the optically transparent adhesive sheet of the present invention exhibit the function of permeating outgassing (moisture) released from a resin substrate (e.g., a polycarbonate substrate), thereby preventing outgassing (moisture) from accumulating at the interface between the optically transparent adhesive sheet of the present invention and the resin substrate and causing delayed bubbles.

[0074] The lower limit of the thickness of the resin substrate is not particularly limited, but is preferably 0.5 mm or more. If the thickness of the resin substrate is less than 0.5 mm, the outgas (moisture) released from the resin substrate is small, so the effect of suppressing delayed foaming obtained by adjusting the thickness of the optically transparent adhesive sheet is relatively small.

[0075] In addition, when the resin substrate used in the present invention has been subjected to heat treatment or surface treatment, the contribution of adjusting the thickness of the optically transparent adhesive sheet in suppressing delayed bubbles may be relatively small. Therefore, from the viewpoint of enjoying the effects of the present invention, it is preferable that the resin substrate used in the present invention is an untreated product that has not been subjected to heat treatment or surface treatment.

[0076] The use of the laminated structure of the present invention is not particularly limited, and may be a liquid crystal module and a cover panel bonded together by an optically transparent adhesive sheet. The resin substrate used in the present invention may be the outermost member of the liquid crystal module, or may be the cover panel. The visibility of the liquid crystal module can be improved by bonding the liquid crystal module and the cover panel together by an optically transparent adhesive sheet and eliminating the air layer between the liquid crystal module and the cover panel. When the liquid crystal module is disposed in a housing (bezel) having an opening in the display section, the bezel is disposed on the outer edge of the liquid crystal module. Therefore, a step corresponding to the thickness of the bezel is formed. The method of bonding the liquid crystal module and the cover panel by overlapping an optically transparent adhesive sheet not only in the center of the liquid crystal module but also in the area where the bezel is disposed is also called "bezel-on bonding". The bonded structure formed by bezel-on bonding is also called "bezel-on bonding structure".

[0077] The optically transparent adhesive sheet used in the present invention is flexible and can be made thick, so it is suitable for bezel-on lamination. The laminated structure of the present invention may have a bezel-on lamination structure, for example, a structure having an optically transparent adhesive sheet and a support member between a first substrate and a second substrate, the support member having a step forming portion disposed on the outer edge of the first substrate, and the optically transparent adhesive sheet may include a thick film portion that bonds the first substrate and the second substrate, and an end portion sandwiched between the step forming portion and the second substrate. The resin substrate may be the first substrate or the second substrate.

[0078] 4 is a cross-sectional view showing a schematic configuration of a laminated structure of the present invention having a bezel-on laminated structure. The laminated structure 50 shown in FIG. 4 has a configuration in which an optically transparent adhesive sheet 10 and an upper bezel (support member) 41 are provided between a first substrate 51 and a second substrate 52, and may be a part of an electronic device such as a display device. The upper bezel 41 is integrated with the lower bezel 42 to form a housing (bezel) that houses the first substrate 51.

[0079] In the laminated structure 50, the optically transparent adhesive sheet 10 includes a thick film portion that bonds the first substrate 51 and the second substrate 52, and an end portion sandwiched between the step-forming portion of the upper bezel 41 and the second substrate 52. The end portion of the optically transparent adhesive sheet 10 is sandwiched between the second substrate 52 and the step-forming portion of the upper bezel 41, and is therefore difficult to peel off. In addition, since the optically transparent adhesive sheet 10 reaches the step-forming portion of the upper bezel 41, the entire upper surface of the first substrate 51 is covered by the step-forming portion of the upper bezel 41 or the optically transparent adhesive sheet 10, and moisture absorption of the first substrate 51 can be prevented. When a polarizing plate is located on the upper surface of the first substrate 51, moisture absorption of the polarizing plate can be prevented. If the polarizing plate absorbs moisture, performance deterioration may be accelerated, or the absorbed moisture may evaporate in a high-temperature environment, causing delayed bubbles.

[0080] The combination of the first substrate 51 and the second substrate 52 is not particularly limited, and examples thereof include various components constituting a display device, such as a display panel, a touch panel (a glass substrate with an ITO transparent conductive film), and a cover panel (cover glass). The type of the display panel is not particularly limited, and examples thereof include a liquid crystal panel, an organic electroluminescence panel (organic EL panel), and the like. In addition, a polarizing plate, a retardation film, and the like may be disposed on the surface of the display panel to which the optically transparent adhesive sheet 10 is attached. By bonding various components in the display device using the optically transparent adhesive sheet 10, it is possible to eliminate an air layer (air gap) in the display device, and the visibility of the display screen can be improved. In addition, when a polarizing plate is disposed, the optically transparent adhesive sheet 10 can effectively prevent moisture absorption of the polarizing plate. A combination in which the first substrate 51 is a display panel such as a liquid crystal module, and the second substrate 52 is a resin substrate (cover panel) made of polycarbonate is preferable.

[0081] The upper bezel 41 is a frame-shaped member arranged around the optically transparent adhesive sheet 10 when viewed in a plan view, and at least a portion of it is arranged on the outer edge of the first substrate 51. The side of the portion (step forming portion) arranged on the outer edge of the first substrate 51 forms a step. The shape of the side of the step forming portion is not particularly limited, and the side of the step forming portion may be perpendicular to the upper surface of the first substrate 51. When the first substrate 51 is a display panel, the upper bezel 41 is arranged in the frame region of the display device, but a light-shielding portion 52A may be provided on the outer edge of the first substrate 51 so that the upper bezel 41 is not visible to the user of the display device. The material of the upper bezel 41 is not particularly limited, and examples thereof include metal, resin, and the like.

[0082] The thickness (size of the step) of the upper bezel 41 is not particularly limited, but is, for example, 200 to 1000 μm. If the thickness of the upper bezel 41 exceeds 200 μm, the thickness of the optically transparent adhesive sheet 10 needs to be 300 μm (0.3 mm) or more, so an optically transparent adhesive sheet thicker than a normal optically transparent adhesive sheet is used.

[0083] The thickness of the thick film portion of the optically transparent adhesive sheet 10 is preferably 1.5 times or more, and more preferably 2 times or more, the thickness of the step-forming portion of the upper bezel 41. This ensures sufficient thickness at the end of the optically transparent adhesive sheet 10 sandwiched between the step-forming portion of the upper bezel 41 and the second substrate 52, and prevents peeling of the end. The thickness of the thick film portion of the optically transparent adhesive sheet 10 in the laminated structure 50 is substantially the same as the thickness of the optically transparent adhesive sheet 10 before lamination. In other words, the thickness of the optically transparent adhesive sheet 10 before lamination is preferably 1.5 times or more, and more preferably 2 times or more, the thickness of the upper bezel 41. EXAMPLES

[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0085] Example 1 First, 75 parts by weight of polyolefin polyol (Idemitsu Kosan Co., Ltd.'s "EPOL (Epol, registered trademark)"), 2.4 parts by weight of IPDI (isophorone diisocyanate)-based polyisocyanate (Sumika Bayer Urethane Co., Ltd.'s "Desmodur I"), 4.6 parts by weight of modified polyisocyanate containing ethylene oxide units (Tosoh Corporation's "Coronate 4022"), 17 parts by weight of tackifier (Idemitsu Kosan Co., Ltd.'s "Imarve P-100"), and 1 part by weight of catalyst (dimethyl tin dilaurate) were stirred and mixed using a reciprocating rotary stirrer agitator to prepare a thermosetting polyurethane composition having an α ratio of 1.60. In addition, in the thermosetting polyurethane composition, the mixing ratio (molar ratio) of the IPDI-based polyisocyanate (A) and the modified polyisocyanate (B) was A:B=2:1.

[0086] Tosoh's "Coronate 4022" is obtained by reacting a polyisocyanate made from hexamethylene diisocyanate and / or a hexamethylene diisocyanate monomer as a starting material with an ether polyol having an average of three or more ethylene oxide units per molecule.

[0087] The obtained thermosetting polyurethane composition was then sandwiched between a pair of release films (PET films with a release treatment applied to the surface) and transported while being crosslinked and cured under conditions of an oven temperature of 50 to 90°C and an oven time of several minutes to obtain a sheet with a release film. The crosslinking reaction was then carried out for 10 to 15 hours in a heating device to produce a thermosetting polyurethane layer (intermediate adhesive layer) with release films on both sides. The thickness of the thermosetting polyurethane layer (intermediate adhesive layer) was 960 μm.

[0088] On the other hand, 0.6 parts by weight of an isocyanate-based curing agent ("DY-70" manufactured by Soken Chemical Industries, Ltd.) and 1 phr of an ultraviolet absorber ("LA-36" manufactured by ADEKA Corporation) were added to 100 parts by weight of an acrylic resin (a blend of "SK1838" and "SK1875" manufactured by Soken Chemical Industries, Ltd. in a solid content ratio of 5:5) to prepare an acrylic resin composition containing an ultraviolet absorber. The obtained acrylic resin composition was applied to a release film using a comma coater, dried in a drying oven at 80 to 120°C, and then a release film was placed on the coated surface. Then, the composition was heated at 40°C for one week to complete curing, and an acrylic adhesive layer was prepared. The thickness of the acrylic adhesive layer was 25 μm.

[0089] Then, two sheets of the acrylic pressure-sensitive adhesive layer with the release film and one sheet of the thermosetting polyurethane layer (intermediate pressure-sensitive adhesive layer) with the release film were prepared. One release film was peeled off from the first acrylic pressure-sensitive adhesive layer with the release film, and a thermosetting polyurethane layer (intermediate pressure-sensitive adhesive layer) was laminated on the surface of the first acrylic pressure-sensitive adhesive layer from which the release film was peeled off. Furthermore, one release film was peeled off from the second acrylic pressure-sensitive adhesive layer with the release film, and a second acrylic pressure-sensitive adhesive layer (second acrylic pressure-sensitive adhesive layer) was laminated on the surface of the thermosetting polyurethane layer opposite to the surface on which the first acrylic pressure-sensitive adhesive layer (first acrylic pressure-sensitive adhesive layer) was laminated. In this way, a laminate according to Example 1 was produced in which the release film, the first acrylic pressure-sensitive adhesive layer, the thermosetting polyurethane layer (intermediate pressure-sensitive adhesive layer), the second acrylic pressure-sensitive adhesive layer, and the release film were laminated in this order. The total thickness of the optically transparent adhesive sheet of Example 1 (the first acrylic adhesive layer, the thermosetting polyurethane layer (intermediate adhesive layer), and the second acrylic adhesive layer) was 1010 μm.

[0090] Example 2 A laminate of Example 2 was prepared in the same manner as Example 1, except that 0.6 parts by weight of an isocyanate curing agent ("DY-70" manufactured by Soken Chemical Engineering Co., Ltd.) and 1 phr of an ultraviolet absorber ("Dynesorb P-6" manufactured by Daiwa Kasei Co., Ltd.) were added to 100 parts by weight of an acrylic resin (a blend of "SK1838" and "SK1875" manufactured by Soken Chemical Engineering Co., Ltd. in a solid content ratio of 5:5) to prepare an acrylic resin composition containing an ultraviolet absorber. Example 3 The laminate of Example 3 was prepared in the same manner as Example 1, except that an acrylic elastomer ("SK Dyne 1875" manufactured by Soken Chemical Industries, Ltd.) was used instead of a thermosetting polyurethane composition as the intermediate adhesive layer composition constituting the intermediate adhesive layer used in the optically transparent adhesive sheet (OCA), and the thickness of the intermediate adhesive layer and the total thickness of the obtained optically transparent adhesive sheet were changed as shown in Table 1 below. The intermediate pressure-sensitive adhesive layer using the acrylic elastomer was prepared as follows. An acrylic resin composition was prepared by adding 0.6 parts by weight of an isocyanate curing agent ("DY-70" manufactured by Soken Chemical Industries, Ltd.) to 100 parts by weight of an acrylic resin ("SK1875" manufactured by Soken Chemical Industries, Ltd.). The obtained acrylic resin composition was coated on a release film and dried in a drying oven at 80 to 120°C, and then coating and drying were repeated until the target thickness was reached. Then, a release film was laminated on the coated surface. Then, the composition was heated at 40°C for one week to complete curing, and an intermediate adhesive layer was prepared. Example 4 The laminate of Example 4 was prepared in the same manner as Example 1, except that the thickness of the intermediate adhesive layer used in the optically transparent adhesive sheet (OCA) and the total thickness of the obtained optically transparent adhesive sheet were changed as shown in Table 1 below.

[0091] Comparative Example 1 Except for not laminating the first and second acrylic adhesive layers (surface acrylic adhesive layers) and changing the thickness of the intermediate adhesive layer to 1000 μm, an intermediate adhesive layer having release films on both sides was produced in the same manner as in Example 1. This was designated as a laminate according to Comparative Example 1.

[0092] Comparative Example 2 A laminate according to Comparative Example 2 was produced in the same manner as in Example 1, except that the amount of the ultraviolet absorber (LA-36 manufactured by ADEKA Corporation) added to the acrylic resin composition was set to 10 phr.

[0093] Comparative Example 3 A laminate for Comparative Example 3 was prepared in the same manner as Comparative Example 1, except that 1 phr of the ultraviolet absorber ("LA-36" manufactured by ADEKA Corporation) used in the above acrylic adhesive layer was added to the thermosetting polyurethane composition forming the intermediate adhesive layer (thermosetting polyurethane layer) used in the optically transparent adhesive sheet (OCA).

[0094] Comparative Example 4 A laminate of Comparative Example 4 was prepared in the same manner as Example 1, except that no ultraviolet absorber was added to the acrylic adhesive layer used in the optically transparent adhesive sheet (OCA), and 1 phr of the ultraviolet absorber ("L-36" manufactured by ADEKA Corporation) used in the above acrylic adhesive layer was added to the thermosetting polyurethane composition forming the intermediate adhesive layer (thermosetting polyurethane layer).

[0095] Comparative Example 5 Except for not laminating the first and second acrylic adhesive layers (surface acrylic adhesive layers) and changing the thickness of the intermediate adhesive layer to 500 μm, an intermediate adhesive layer having release films on both sides was produced in the same manner as in Example 3. This was designated as a laminate according to Comparative Example 5.

[0096] The polycarbonate substrates used in the examples and comparative examples are as follows: Thickness 0.5mm: "Resin sheet PCTSH" manufactured by Misumi Group Headquarters

[0097] (Reliability evaluation test and dispersion (HAZE) test) One release film of each laminate produced in the examples and comparative examples was peeled off from a transparent glass substrate (soda glass manufactured by Matsunami Glass Industry Co., Ltd.), and one side of the optically transparent adhesive sheet was vacuum-bonded at a pressure of 0.15 MPa. Next, a 1 mm-thick polycarbonate substrate ("Resin Sheet PCTSH" manufactured by Misumi Group Inc.) was vacuum-bonded at a pressure of 0.15 MPa to the other side of the optically transparent adhesive sheet from which the remaining release film had been peeled off. This bonding resulted in a bonded structure in which the polycarbonate substrate and the glass substrate were bonded by the optically transparent adhesive sheets according to the examples and comparative examples.

[0098] Rectangular test specimens (diagonal length: 7 inches) of the laminated structures obtained according to the examples and comparative examples were prepared one by one and left in a high temperature and high humidity environment of 85 ° C and 85% for 24 hours. After leaving the specimens, they were visually observed to confirm whether air bubbles (delayed bubbles) were generated at the adhesive interface between the glass substrate and the optically transparent adhesive sheet, and at the adhesive interface between the polycarbonate substrate and the optically transparent adhesive sheet. The test results are shown in Table 1 below. Conditions in which no air bubbles (delayed bubbles) were generated were marked with "O", and conditions in which at least one air bubble (delayed bubble) was generated were marked with "X". In addition, a haze measurement was performed according to JIS K 7136, and conditions in which the haze exceeded 2% were marked with "X", and conditions in which the haze was less than 2% were marked with "O". The evaluation results are shown in Table 1 below.

[0099] (UV protection evaluation test) One release film of each laminate prepared in the examples and comparative examples was peeled off from a transparent glass substrate (soda glass manufactured by Matsunami Glass Industry Co., Ltd.), and one side of the optically transparent adhesive sheet was vacuum-attached to the transparent glass substrate (soda glass manufactured by Matsunami Glass Industry Co., Ltd.) at a pressure of 0.15 MPa. Next, the other side of the optically transparent adhesive sheet from which the remaining release film had been peeled off was vacuum-attached to the transparent glass substrate at a pressure of 0.15 MPa. This attachment resulted in a laminate structure in which the glass substrate, the optically transparent adhesive sheets according to the examples and comparative examples, and the glass substrate were laminated in this order.

[0100] For each of the obtained laminated structures (glass / optically transparent adhesive sheet / glass), an ultraviolet transmittance test was conducted in accordance with JIS A 5759. Conditions in which the transmittance was 2% or more were marked with "X", and conditions in which the transmittance was less than 2% were marked with "O". The evaluation results are shown in Table 1 below.

[0101] (Weather resistance evaluation) Each of the obtained laminated structures (glass / optically transparent adhesive sheet / glass) was subjected to a weather resistance test in accordance with ISO-4892-2, and the laminated structures (glass / optically transparent adhesive sheet / glass) were subjected to a xenon WOM (irradiation intensity 60 W / m 2 (300-400 nm, BPT: 63° C.) for 1000 hours, and a color change (Δb) of 1 or more was marked as "x", and a color change of less than 1 was marked as "good". The evaluation results are shown in Table 1 below.

[0102] (Adhesion strength evaluation) For each of the optically transparent adhesive sheets according to the examples and comparative examples, a 180° peel test was performed in accordance with JIS Z2037 to measure the adhesive strength (N / 25 mm). Specifically, the 180° peel test was performed using the method shown in FIG. 3. The optically transparent adhesive sheets prepared in the examples and comparative examples were cut to a length of 75 mm x width of 25 mm to prepare test pieces. After peeling off the release film on one side of the test piece, the test piece was attached to a slide glass 31 having a length of 75 mm x width of 25 mm, and held at a pressure of 0.4 MPa for 30 minutes to bond the optically transparent adhesive sheet to the slide glass 31. Next, the release film on the side opposite the glass slide 31 was peeled off, and a 125 μm thick PET sheet 32 ​​(Melinex (registered trademark) S manufactured by Teijin DuPont Films) was laminated. After that, it was left for 12 hours at room temperature and humidity (temperature 23°C, humidity 50%), and then the PET sheet was pulled in a 180° direction at a speed of 30 mm / min in an environment of 23°C, the optically transparent adhesive sheet was peeled off at the interface with the glass slide 31, and the adhesive strength of the optically transparent adhesive sheet to the glass slide 31 was measured. Note that if the measured peel adhesive strength was less than 20 N / 25 mm, it was evaluated as "X", and if it was 20 N / 25 mm or more, it was evaluated as "O". The evaluation results are shown in Table 1 below.

[0103] [Table 1]

[0104] As can be seen from Table 1 above, the optically transparent adhesive sheets of Examples 1 to 4, which have a first acrylic adhesive layer constituting a first surface, an intermediate adhesive layer, and a second acrylic adhesive layer constituting a second surface, in that order, and in which the first acrylic resin layer and the second acrylic resin layer contain a specific amount of ultraviolet absorber, and have a total thickness of 200 to 2100 μm, did not produce delayed bubbles even when left in a high temperature and high humidity environment of 85°C and 85% for 24 hours, had a good reliability evaluation, had an adhesive strength of 20 N / 25 mm or more, and a haze of less than 2%, and were excellent in both weather resistance evaluation and ultraviolet blocking ability. On the other hand, the optically transparent adhesive sheets of Comparative Examples 1 and 5, which did not have first and second acrylic adhesive layers and did not contain an ultraviolet absorber, had poor ultraviolet blocking ability and also poor weather resistance evaluation, haze, adhesion strength, and reliability evaluation. In addition, the optically transparent adhesive sheet of Comparative Example 2, which had an ultraviolet absorber in the first and second acrylic adhesive layers, had an ultraviolet absorber content of 10 phr, which was significantly higher than 3 phr, and had poor haze, adhesion and reliability ratings. In addition, the optically transparent adhesive sheets of Comparative Examples 3 and 4, which have an ultraviolet absorber in the intermediate adhesive layer rather than in the first and second acrylic adhesive layers, had good weather resistance evaluations and ultraviolet blocking ability, but poor haze, adhesion strength and reliability evaluations. [Explanation of symbols]

[0105] 10: Optically transparent adhesive sheet 11: First acrylic adhesive layer 12: Intermediate adhesive layer 13: Second acrylic adhesive layer 20: Laminate 21: First release film 22: Second release film 31: Slide glass 32: PET sheet 41: Upper bezel (support member) 42: Lower bezel 50: Bonded structures 51: First substrate 52: Second substrate 52A: Light shielding part

Claims

1. a first acrylic pressure-sensitive adhesive layer constituting a first surface, an intermediate pressure-sensitive adhesive layer, and a second acrylic pressure-sensitive adhesive layer constituting a second surface, in this order; the first acrylic pressure-sensitive adhesive layer and the second acrylic pressure-sensitive adhesive layer each contain 0.1 to 3 parts by weight of an ultraviolet absorbing agent based on 100 parts by weight of an acrylic resin; The total thickness is 200 to 2100 μm, An optically transparent adhesive sheet having an adhesive strength of 20 N / 25 mm or more.

2. The optically transparent adhesive sheet according to claim 1, characterized in that the thickness of each of the first acrylic adhesive layer and the second acrylic adhesive layer is 3 μm or more and 40 μm or less.

3. The optically transparent adhesive sheet described in claim 1 or 2, characterized in that the ultraviolet absorber is a benzotriazole-based ultraviolet absorber and / or a benzophenone-based ultraviolet absorber.

4. The optically transparent adhesive sheet described in any one of claims 1 to 3, characterized in that the optically transparent adhesive sheet has a haze of less than 2%.

5. The optically transparent adhesive sheet according to claim 1 or 2, characterized in that the intermediate adhesive layer contains a thermosetting polyurethane.

6. A laminate characterized by comprising an optically transparent adhesive sheet described in any one of claims 1 to 5, a first release film covering one side of the optically transparent adhesive sheet, and a second release film covering the other side of the optically transparent adhesive sheet.

7. A laminated structure comprising an optically transparent adhesive sheet according to any one of claims 1 to 5 and a resin substrate adhered to the first surface.

Citation Information

Patent Citations

  • Adhesive tape

    JP2016155958A

  • Adhesive sheet for display screen, laminate, display body and screen protection method

    JP2017179242A

  • Transparent adhesive optical sheet, laminate and bonded structure

    WO2019026577A1